Piracy in the Indian film industry : copyright and cultural consonance - Scaria, Arul George (Cambridge university press, 2014)
Piracy in the Indian Film Industry: Copyright and Cultural Consonance sheds light on how copyright law works at the grassroots level in India, by exploring the social, cultural, historical, legal and economic dimensions of piracy in one of the biggest copyright-based industries: the Indian film industry. Based on extensive fieldwork, this book provides novel and insightful findings on the complexity and diversity of perceptions regarding piracy within Indian society. About the Author: Arul George Scaria is a postdoctoral researcher at the Catholic University of Louvain (UCL) in Belgium. He completed his doctoral studies at the International Max Planck Research School for Competition and Innovation (IMPRS-CI), Munich. He has previously worked as a CSIR-NIF Fellow at the National Innovation Foundation India and also practised as a lawyer in the High Court of Kerala, India. "Provides insights into the copyright law by analysing the social, cultural, historical, legal, and economic dimensions of copyright piracy in the Indian film industry"--